Risk factors for hospitalization among adults aged ≥65 years with non‐typhoidal Salmonella infection linked to backyard poultry contact. (21st January 2022) - Whitehill, Florence M.; Stapleton, G. Sean; Koski, Lia; Sievert, Dawn; Nichols, Megin
Abstract: Objective: We describe the epidemiology of live poultry‐associated salmonellosis (LPAS) and investigate potential risk factors associated with hospitalization among adults aged ≥65 years in the United States during 2008–2017. LPAS is a public health concern in the United States, especially among people with increased risk for hospitalization, such as older adults. Sample: We analysed data from people aged ≥65 years with non‐typhoidal salmonellosis who reported live poultry contact within seven days prior to illness onset. Procedure: We used logistic regression to estimate the odds of hospitalization associated with several risk factors including types of live poultry contact exposures. Results: LPAS among older adults in this analysis resulted in high hospitalization rates. Salmonella Hadar infection was associated with increased hospitalization. Among older adults with LPAS, 109 individuals of 127 (86%) reported contact with live poultry at their or someone else's residence, and 85 of 105 with available information (81%) reported owning poultry. Conclusions and Clinical Relevance: Additional infection prevention information and education targeted at poultry‐owning older adults are needed to prevent illness and hospitalization.